Temperature Resistance of Bethamcherla Stone Powder Waste Geopolymer Concrete - J. Vara Prasad, E. Aruna Kanthi (International Journal of Advanced Science and Technology, 2020)
Bethamcherla stone powder (BSP) is used as precursor to source materials of fly ash, slag, metakaoline etc., to the geopolymer concrete (GPC). In present investigation the ground granulated blast furnace slag (GGBFS) was replaced with BSP waste in proportion of 0, 25, 50 and 75 by weight of GGBFS. The study mainly focused on cube compressive strength behavior of GPC when exposed to elevated temperatures of 200,400,600,800 and 10000C. From the results it is noticed that, for mixes with 25 and 50% replacement show increase in compressive strength for 200 and 4000C and for remaining temperatures strengths are decreasing. But for mix with 75% replacement, cube compressive strengths are decreasing as temperature increases. Mathematical models are developed to assess the experimental results and after verification it is found that, models provided satisfactory results.